Hyperlipidemic pancreatitis in children: characteristics of the course and a clinical case presentation - Lembryk, I. S.; Tsytsiura, O. O.; Zhyliak, O. V.; Dutchuk, O. V.; Buiak, P. Z.; Dutchak Н. M.; Krasivskyi, I. Y. (Zaporozhye Medical Journal, 2022)
The article presents data on the prevalence, clinical, diagnostic and treatment characteristics of acute hyperlipidemic pancreatitis in children, based on a literature review and a clinical case presentation. The aim of this work is to define the nature of hyperlipidemic pancreatitis in children based on the literature review, and the clinical case presentation. Material and methods. The analysis of the literature data of the last 10 years through the Google Scholar and PubMed databases was performed. The clinical course, blood tests assessing protein and lipid indicators, abdominal ultrasound findings typical for acute hyperlipidemic pancreatitis were examined in a patient O. S., born in 2007. Results. The disease was diagnosis based on the study of anamnestic, clinical, laboratory and ultrasound findings. Lipid profile test revealed an increase in the level of cholesterol and triglycerides, and a decrease in the level of high-density lipoproteins. Abdominal ultrasound showed changes in the pancreatic tissues: the pancreas was significantly enlarged with a heterogeneous structure of the parenchyma, the echogenicity was significantly increased due to edema, and there was a small amount of effusion. Laparoscopic drainage of the omentum and abdominal cavity was recommended and performed. The key to the successful treatment was repeated long-term use of detoxification and hypolipidemic therapy in combination with dietary corrections (a low-fat diet). Conclusions. As of today, acute hyperlipidemic pancreatitis continues to be one of the least studied and rare pathologies among the pediatric population. This necessitates the search for and implementation of both diagnostic and treatment algorithms into clinical practice to timely correct and prevent complications.